2018
DOI: 10.1017/thg.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Cold and Heat Patterns: A Twin Study

Abstract: In traditional East Asian medicine, cold-heat patterns have been widely used in the diagnosis and treatment of patients suffering from various diseases. The present study aimed to estimate the heritability of cold-heat patterns. Trained interviewers administered a cold-heat pattern questionnaire to 1,753 twins (mean age = 19.1 ± 3.1 years) recruited throughout South Korea. Correlations for the cold pattern (CP) were 0.42 (95% CI [0.28, 0.54]) for monozygotic (MZ) males, 0.16 (95% CI [-0.08, 0.39]) for dizygoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…Figure 1 presents , respectively. These estimates were very close to the estimates found in our previous studies based on univariate biometrical models (Hur et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Figure 1 presents , respectively. These estimates were very close to the estimates found in our previous studies based on univariate biometrical models (Hur et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In support of the findings from twin studies, gene identification studies have successfully detected several FTO gene variants related to BMI (e.g., Qi et al, 2014). Using the sample employed in the present study, we recently showed that the CP and the HP are heritable traits, with heritability estimates being 40% (95% CI [38,42] [25,42) for the latter (Hur et al, 2018). As with many other complex traits, shared environmental influences on the CP and the HP were negligible, and environmental factors that influenced the CP and the HP were mainly individual specific.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The cold pattern (CP) is characterized by a preference for warm temperature, intolerance of cold, hypothermia, paleness, diarrhea, peripheral chills, and spasms (8). Especially, cold hypersensitivity in the hands and feet (CHHF) is a condition in which affected individuals feel excessively cold at low temperatures because of spastic peripheral vasoconstriction.…”
mentioning
confidence: 99%